The Language Shift Origins of Judeo-Spanish - Şaul, Mahir (Anuario del Seminario de Filología Vasca "Julio de Urquijo.", 2025)
This article proposes that the Judeo-Spanish language of the Sephardic Jews of the Balkans and the eastern Mediterranean involved at its origin a language shift that occurred after emigration from the Iberian Peninsula, in non-Hispanic environment; that a form of Castilian was adopted as a deliberate act and rapidly in the early period of exile, to change a prior situation of Romance language pluralism within and among the transplanted Jewish communities.